Exploring the Diversity and Distribution of Macrophytes of Chandanpur Beel and Churamon Beel, North Dinajpur District, West Bengal: Implications for Conservation - Mandal, Sujit Kumar; Mukherjee, Sudeshna (International Journal of Scientific Research in Biological Sciences, 2024)
Aquatic macrophytes are the most diverse group of large photosynthetic organism and fundamental ingredients of any wetland biosphere. Overexploitation of wetlands and discharge of effluents into the water of wetland is the most serious problem nowadays which directly interfering the normal growth and sustainability of the macrophytes. The present research investigates the diversity and distribution pattern of macrophytes of Chandanpur beel and Churamon beel of North Dinajpur District. This investigation disclosed a total of 19 species belonging from 14 different families among which Asteraceae, Commelinaceae, Onagraceae, Poaceae and Polygonaceae showed the equal distribution each comprise 2 sp. whereas rest of the families each contain only 1 sp. Life form (Raunkiaer,1934) and growth form (Cook,1996) classification of macrophytes also have been done. Different quantitative characters viz. frequency, density, abundance, RF, RD, RA and IVI were also evaluated where Torenia crustacea showed the highest IVI value (27.19) followed by Pontederia crassipes (19.42). Diversity analysis revealed highest species diversity and species richness in Chandanpur beel. The study provides the insight pattern of diversity as well as present status of macrophytes which will be the triggering factor for the implementation effective step regarding conservation of macrophytes in their native area.